(untitled) (International Journal of Biomedical Research, 2015)
Deep vein thrombosis (DVT) is a common cause of morbidity and mortality, particularly in older people. Many genetic polymorphisms are considered as a risk factor of Hypercoagulability in DVT. MTHFR C677T polymorphism is reported to be associated with hyperhomocysteinemia through its inability to convert homocystein to methionnine which lead to hypercoagulable state that may promote DVT. The aim of this study was to examine the association of MTHFR (C677T) polymorphism with the risk of DVT in Sudan. The study included 50 DVT patients, their MTHFR C677T genotype frequencies (detected by PCR/RFLP) and haematological charecteristics (measured by Sysmex KX-21N) were determined and compared with 50 age and sex matched normal subjects as control. Low frequency of mutant MTHFR C677T genotype with 0% TT genotype (homozygote) and 12% CT (heterozygote) was observed. Our study showed a statistically insignifi